2018
DOI: 10.1021/jacs.8b12152
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Enantioselective Iridium-Catalyzed Amination of Racemic Branched Alkyl-Substituted Allylic Acetates with Primary and Secondary Aromatic and Heteroaromatic Amines

Abstract: The air and water stable π-allyliridium C,O-benzoate modified by (S)-tol-BINAP, (S)-Ir-II, catalyzes highly regio- and enantioselective Tsuji-Trost type aminations of racemic branched alkyl-substituted allylic acetates using primary or secondary (hetero)aromatic amines. Specifically, in the presence of (S)-Ir-II (5 mol%) in DME solvent at 60-70 °C, α-methyl allyl acetate 1a (100 mol%) reacts with primary (hetero)aromatic amines 2a-2l (200 mol%) or secondary (hetero)aromatic amines 3a-3l (200 mol%) to form the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 80 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…[27] Thus, at present we are only able to achieve high levels of C2regioselectivity using aryl substituted allylic alcohols.N onetheless,wewere pleased to observe that allylic substitution is still possible under our usual reaction conditions with aliphatic allylic alcohol 1p,g iven that p-allyl complex formation is known to be more challenging for such alcohols compared with the more activated benzylic systems that are the main focus of this study. [28] On the basis of the experimental data described above,in addition to previously described theoretical evidence, [29] the following mechanism for the enantioselective direct C2allylation of indole is proposed (Scheme 6). Thec atalyst precursor [Ir(cod)Cl] 2…”
Section: Angewandte Chemiementioning
confidence: 83%
“…[27] Thus, at present we are only able to achieve high levels of C2regioselectivity using aryl substituted allylic alcohols.N onetheless,wewere pleased to observe that allylic substitution is still possible under our usual reaction conditions with aliphatic allylic alcohol 1p,g iven that p-allyl complex formation is known to be more challenging for such alcohols compared with the more activated benzylic systems that are the main focus of this study. [28] On the basis of the experimental data described above,in addition to previously described theoretical evidence, [29] the following mechanism for the enantioselective direct C2allylation of indole is proposed (Scheme 6). Thec atalyst precursor [Ir(cod)Cl] 2…”
Section: Angewandte Chemiementioning
confidence: 83%
“…Stivala and team corroborated an Ir‐catalyzed amination of alkyl substituted allylic acetate with primary, secondary and heteroaromatic amines [56] . α‐Methyl allyl acetate was taken as the substrate specifically in the presence of 5 mol% of ( S )‐Ir‐(II) in DME solvent at 60–70 °C for 24–40 h (Scheme 27).…”
Section: Classificationmentioning
confidence: 86%
“…Using SEGPHOS‐modified π‐allyliridium‐ C,O ‐benzoate catalysts, allylic aminations mediated by aliphatic amine nucleophiles occur with high levels of regio‐ and enantioselectivity . It was later found that the tol‐BINAP‐modified π‐allyliridium‐ C,O ‐benzoate ( S )‐Ir‐ I is a superior catalyst, enabling highly regio‐ and enantioselective allylation of electronically diverse primary and secondary (hetero)aryl amines …”
Section: Figurementioning
confidence: 99%